Case report: Curing a rare, unstable hemoglobin variant Hb Bristol-Alesha using haploidentical hematopoietic stem cell transplantation - Zhang, Qin; Huo, Yujia; Sun, Qinggang; Liu, Nan; Shi, Hongchuan; Wang, Minghui; Xiao, Jinming; Yuan, Hanzi; Tang, Xiangfeng (Frontiers in Immunology, 2023)
Unstable hemoglobinopathies are a rare, heterogeneous group of diseases that disrupt the stability of hemoglobin (Hb), leading to chronic hemolysis and anemia. Patients with severe phenotypes often require regular blood transfusions and iron chelation therapy. Although rare, studies have reported that hematopoietic stem cell transplantation (HSCT) seems to be an available curative approach in transfusion-dependent patients with unstable hemoglobinopathies. Here, we describe successful haploidentical HSCT for the treatment of an unstable Hb variant, Hb Bristol-Alesha, in a 6-year-old boy with severe anemia since early childhood. Two years after transplantation, he had a nearly normal hemoglobin level without evidence of hemolysis. DNA analysis showed complete chimerism of the donor cell origin, confirming full engraftment with normal erythropoiesis.